Document analysis of exertional heat illness policies and guidelines published by sports organisations in Victoria, Australia. Issue 1 (1st April 2020) - Gamage, Prasanna J; Finch, Caroline F; Fortington, Lauren V
Abstract : Objectives: To conduct a document and content analysis of exertional heat illness (EHI)-related documents published by sports organisations in Victoria, Australia, in order to determine their scope and evidence base against current international best practice recommendations. Methods: A qualitative document and content analysis. Official documents relating to EHI were identified through a search of 22 Victorian sport organisation websites, supplemented by a general internet search. The content of these documents was evaluated against recommendations presented in three current international position statements on prevention and management of EHI. Results: A range of document types addressing EHI were identified (n=25), including specific heat policies, match day guides, rules and regulations. Recommendations about prevention measures were the most common information presented, but these were largely focused on event modification/cancellation guidelines only (n=22; 88%). Most documents provided information on hydration as a preventive measure (n=20; 80%), but the emphasis on the importance of cooling strategies (n=7; 28%) and heat acclimatisation (n=5; 20%) was inadequate. Details on EHI, including its definition, symptoms/signs to look out for, and common risk factors (beyond humidity/high temperatures) were lacking in most documents. Conclusion: There is considerable variation in formal documents with regard to their content and quality of information. Continued efforts to bridge the evidence to practice gap in sports safety are therefore important. This study highlights the challenge for community sport, which relies on high-level policy and governance, across settings and populations that can differ substantially in their needs.